Modular structure of investment decision support system - Zakharova, Tetiana; Moskalenko, Valentyna (Видавництво Львівської політехніки, 2010)
This paper reviews mathematical support for implementation of decision-making support system modules in investment company.
Keywords: мodeling; investment; projects portfolio; investment policy